Tradisi Sedekah Bumi Sebagai Refleksi Nilai Spiritual dan Sosial di Masyarakat Perkotaan (Studi Etnografi di Kelurahan Pradah Kalikendal Surabaya): Pengabdian - Abelia Dhuwi Juwita; Alfian Aulya Rahman; Ayudhia Sakha Widyadana; Khansa Tsabita; Rizka Salsabila Putri; Joko Mijiarto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Sedekah Bumi tradition is a form of local wisdom developed in various regions of Indonesia to express gratitude for the abundance of the earth's produce and life. This community service activity was carried out in RW 2, Prada Kalikendal, Surabaya, to explore, document, and support the preservation of the Earth Alms tradition. The methods used included field observation, interviews with community leaders, and participatory documentation. The results of the activity indicate that the sedekah bumi tradition in this region contains strong spiritual and cultural values as a means to strengthen social relations between generations. These findings emphasize the importance of preserving local wisdom amidst modernization and changes in urban lifestyles. The conclusion of this activity emphasizes that collaboration between the community and academics plays a crucial role in maintaining the sustainability of cultural traditions contextually and adaptively to changing times.